Modifikasi Model Propagasi Ericsson Jaringan Lte-1800 Mhz Pada Daerah Lepas Pantai Dengan Menggunakan Least Square Method - Romadona, Ade Yuda Wahyu; Alfaresi, Bengawan; Ardianto, Feby (Universitas PGRI Palembang, 2020)
The 4G network has the advantage of accessing data at a higher speed compared to its predecessor, namely 3G. The purpose of this is to see the fluctuation of LTE-1800 MHz signal in the offshore area then modify the Ericsson propagation modeling to get the results with real conditions (real) and accurate. As well as making comparisons of calculation results from existing Ericsson Propagation modeling and comparisons of the results of modifying modeling that can. The method used in this research is four stages: 1). determination of initial data, 2). tools and materials, 3). data grouping and 4). pathloss calculation. The research was conducted in a coastal area off the shore in Panjang district, Bandar Lampung district. Testing the quality of the 4G-LTE network in offshore coastal areas is carried out by measuring several important influencing parameters such as RSRP (Reference Signal Recived Power). All activities are carried out using software devices. Probe by wawe. Analysis of the results before the value 173.5986043 dB obtained from the modeling results from the accurate results of 16.48853263 dB in this calculation using the Ericsson propagation model.